Application of Mass Spectrometry in Pancreatic Cancer Translational Research - Ge, Peng; Luo, Yalan; Chen, Haiyang; Liu, Jiayue; Guo, Haoya; Xu, Caiming; Qu, Jialin; Zhang, Guixin; Chen, Hailong (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is a common malignant tumor of the digestive tract in the world, and its morbidity and mortality are on the rise. In recent years, with the development of surgery, chemotherapy, radiotherapy, targeted therapy and immunotherapy as well as the change of medical thinking mode, remarkable progress has been made in the research of comprehensive diagnosis and treatment of PC. However, the current situation of diagnosis and treatment of PC is still grim. There is an urgent need for academia to fully integrate the basic research and clinical data of PC to form a research model conducive to clinical translation and promote the accurate treatment of PC. In this paper, the translation progress of mass spectrometry in the pathogenesis, diagnosis and treatment of PC was summarized.